Clinical outcomes associated with sarcomere mutations in hypertrophic cardiomyopathy: a meta-analysis on 7675 individuals - Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Tugrul, Oguz Firat; Lai, Chung Lun Alan; Amr, Ali; Haas, Jan; Proctor, Tanja; Ehlermann, Philipp; Jensen, Katrin; Katus, Hugo; Meder, Benjamin (Clinical research in cardiology, 2018)
BackgroundHypertrophic cardiomyopathy (HCM) is the most common genetic cardiovascular disease, which goes along with increased risk for sudden cardiac death (SCD). Despite the knowledge about the different causal genes, the relationship between individual genotypes and phenotypes is incomplete.Methods and resultsWe retrieved PubMed/Medline literatures on genotype-phenotype associations in patients with HCM and mutations in MYBPC3, MYH7, TNNT2, and TNNI3. Altogether, 51 studies with 7675 HCM patients were included in our meta-analysis. The average frequency of mutations in MYBPC3 (20%) and MYH7 (14%) was higher than TNNT2 and TNNI3 (2% each). The mean age of HCM onset for MYH7 mutation positive patients was the beginning of the fourth decade, significantly earlier than patients without sarcomeric mutations. A high male proportion was observed in TNNT2 (69%), MYBPC3 (62%) and mutation negative group (64%). Cardiac conduction disease, ventricular arrhythmia and heart transplantation (HTx) rate were higher in HCM patients with MYH7 mutations in comparison to MYBPC3 (p < 0.05). Furthermore, SCD was significantly higher in patients with sarcomeric mutations (p < 0.01).ConclusionA pooled dataset and a comprehensive genotype-phenotype analysis show that the age at disease onset of HCM patients with MYH7 is earlier and leads to a more severe phenotype than in patient without such mutations. Furthermore, patients with sarcomeric mutations are more susceptible to SCD. The present study further supports the clinical interpretation of sarcomeric mutations in HCM patients.
Published online: 24 August 2017
Gesehen am 22.06.2018